2005
DOI: 10.1103/physrevb.72.045402
|View full text |Cite
|
Sign up to set email alerts
|

Full-potential linearized augmented plane-wave method for one-dimensional systems: Gold nanowire and iron monowires in a gold tube

Abstract: We present an implementation of the full-potential linearized augmented plane-wave ͑FLAPW͒ method for carrying out ab initio calculations of the ground state electronic properties of ͑magnetic͒ metallic nanowires and nanotubes based on the density-functional theory ͑DFT͒. The method is truly one-dimensional, uses explicitly a wire geometry and is realized as an extension of the FLEUR code. It includes a wide variety of chiral symmetries known for tubular and other one-dimensional systems. A comparative study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 43 publications
5
58
0
Order By: Relevance
“…2(a)]. The same result was obtained by previous ab initio calculations of pure Au chains [16,[21][22][23]. While transport experiments in Au chains indicate that these bands do not cross the Fermi level [24], it has been found that doping with oxygen pushes these bands up, establishing conduction through the 5d xz and 5d yz electrons of Au [25,26].…”
supporting
confidence: 69%
“…2(a)]. The same result was obtained by previous ab initio calculations of pure Au chains [16,[21][22][23]. While transport experiments in Au chains indicate that these bands do not cross the Fermi level [24], it has been found that doping with oxygen pushes these bands up, establishing conduction through the 5d xz and 5d yz electrons of Au [25,26].…”
supporting
confidence: 69%
“…The explicit one-and two-dimensional implementations also contain a third region, the vacuum region (VR), which can be treated analogously to the IR. 38,39 Thus, the self-consistent spin density is approximated as…”
Section: B Noncollinear Wannier Functions Within the Flapw Methodsmentioning
confidence: 99%
“…Various nano conductors have constant valued DOS functions in the energy range of interest [7,13,14,15] hence by taking the DOS function of Eq. (1) as constant and evaluating the integral, an I-V expression without integral calculation for nano conductors is derived as shown in Eq.…”
Section: Presented I-v Expression For Ballistic Nano Conductorsmentioning
confidence: 99%